STUDI KELAYAKAN TARI LEPAS REYOG PONOROGO SEBAGAI MODEL PENDIDIKAN DASAR DAN MENENGAH DI KABUPATEN PONOROGO - M., Maryono (Greget, 2015)
To day, the problem that we get is lower appreciation of youth as next generation towardtheir culture themselves. They very like, familiar and feel more as ancient tradition, out of dateand no prestige. Consequently, since people not be oriented any more to values of Javanese culture,costum, and leave the art containing adi luhung values, their attitude turn into brutal, emotional, do not have ashed culture ang less respect of older. Basically, our society life has experienced an apprehensive moral degradation. Therefore, we recently need art education to realizecharacter building among student, giving appreciation and understanding of art for them as nextgeneration. Using art education of reyog based on norms, values, ethics, and aesthetic of cultureenvironment containing adi luhung values, student character as leader generation with nationspirit and Indonesian characteristic will be built. Reyog is dance drama. To apply it to be art local subject matter, it needs for sufficientpackage that devide into some independent dance: Warok, Jathilan, Bujangganong, Kelana Sewandana, and dhadhak Merak. These dances are adapted with curricula guidance from National Education of Ponorogo. Elementery student are demanded to recognize and understandabout basic manner of reyog, however, high shool student are hoped know about basic manner andpresent independent dance of reyog based on valid rule in evaluation creteria of reyog.Keywords: education, local subject matter, reyog, and sufficiency.